The KONTRIBUSI DINASTI FATIMIYAH DI BIDANG PENDIDIKAN: Sebuah Potret Sejarah Pendidikan Islam - Arif Shaifudin (Jurnal Paradigma, 2022)
The historical context of Islamic education cannot be repeated, but the values ??of every event in history can continue to be carried and preserved at any time. The current practice of Islamic education cannot be separated from the historical foundations that have long been built in the past. In the midst of the swift global currents that carry cultural content between countries, it becomes a separate threat to Islamic education as a moral and social guardian. Western culture is like a prima donna for the younger generation who are still students. Ironically, Islamic education, which in his view is a pride and belief in its truth for Muslim students, is increasingly being abandoned. This anxiety is enough to make the writer feel compelled to offer interesting facts about the past about Islamic education during the Fatimid era in Africa, Egypt. A dynasty that thrived in various fields after the fall of the Abbasids. We can still feel the fact that the Fatimid era contributed to the world of Islamic education today is Al-Azhar University, which used to be a building in the form of a mosque. During the reign of the caliph al-Aziz, the al-Azhar mosque underwent a fundamental change, namely a mosque which has developed into a university that offers a variety of knowledge.